Leveled Storybook: A Supplementary Material for Teaching BIPA to Primary School Students - Ni Ketut, Apriliyani (Bahasa: Jurnal Keilmuan Pendidikan Bahasa dan Sastra Indonesia, 2024)
Bahasa Indonesia subject in Green School Bali is taught as a foreign language and integrated with a thematic approach. Based on the observation, storybooks are rarely utilized as learning materials for BIPA (Bahasa Indonesia bagi Penutur Asing) due to the limited availability of resources that meet students' needs. This study aims to design leveled storybook as supplementary teaching materials for BIPA instruction at the primary school level. The research method follows the design and development framework proposed by Richey and Klein, encompassing four main stages: analysis, design, development, and evaluation. Based on the analysis using Candiasa's formula, the developed leveled storybook was categorized as a good quality. The quality evaluation of the storybook was conducted through user judgment, which serves as a limitation of this study. The leveled storybook is expected to serve as effective learning materials to support the teaching of Indonesian as a foreign language at the primary school level.AbstrakPembelajaran bahasa Indonesia di Green School Bali diajarkan sebagai bahasa asing dan diintegrasikan dengan pendekatan tematik. Hasil observasi menunjukkan bahwa buku cerita masih jarang dimanfaatkan sebagai bahan pembelajaran BIPA karena keterbatasan sumber bacaan yang sesuai dengan kebutuhan siswa. Penelitian ini bertujuan untuk merancang buku cerita berjenjang sebagai bahan ajar pendukung dalam mengajar BIPA kepada siswa sekolah dasar. Metode yang digunakan adalah desain penelitian dan pengembangan berdasarkan model Richey dan Klein, yang mencakup empat langkah utama: analisis, desain, pengembangan, dan evaluasi. Berdasarkan hasil analisis dengan menggunakan rumus dari Candiasa, produk buku cerita berjenjang yang dikembangkan dinilai berkualitas baik. Penilaian kualitas buku cerita ini dilakukan melalui user judgment, yang menjadi batasan dalam penelitian ini. Buku cerita berjenjang ini diharapkan dapat menjadi bahan pembelajaran untuk mendukung pengajaran bahasa Indonesia sebagai bahasa asing di tingkat sekolah dasar.